2013
DOI: 10.1364/oe.21.024985
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally-spatial fourier-holography

Abstract: We propose a novel method to obtain non-lens holographic images of micro-objects in white light with diffraction limit quality, based on fourier-spectroscopy principles. We developed a simple method for numerical acquisition of digital holograms of micro-objects at any spectral component from the set of two-dimensional interferograms, registered by fourier-spectrometer. In our experiments we used spectrally-spatial holographic fourier-spectrometer (SSHFS), equipped with supercontinuum light source and CCD came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…We shown that theoretically in few recent works [3][4][5] and experimentally obtained hyperspectral holograms of several microobjects [6]. In current work we discuss new results of recent research.…”
Section: Introductionmentioning
confidence: 69%
“…We shown that theoretically in few recent works [3][4][5] and experimentally obtained hyperspectral holograms of several microobjects [6]. In current work we discuss new results of recent research.…”
Section: Introductionmentioning
confidence: 69%
“…where R t.k stays for the harmonic reference signal varying from experiment-to-experiment [29], [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, HS coherent diffractive imaging (HSCDI) shows a strong progress, for instance, in high-resolution microscopy. Interference between reference and object wavefronts registered as intensity diffraction patterns is used conventionally in spectrally resolved interferometry, 1,2 Fourier transform holography, 3,4 and HS digital holography. 2,5,6 Along with the traditional intensity imaging, HSCDI provides phase imaging, which brings additional information about an object under investigation, e.g., label-free multispectral refractive index estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Interference between reference and object wavefronts registered as intensity diffraction patterns is used conventionally in spectrally resolved interferometry, 1,2 Fourier transform holography, 3,4 and HS digital holography. 2,5,6 Along with the traditional intensity imaging, HSCDI provides phase imaging, which brings additional information about an object under investigation, e.g., label-free multispectral refractive index estimation. 7 In this paper, we consider a class of HSCDI in a shearography optical setup, 8 where two coherent beams, the main (basic) and its time-delay copy, go through a transparent object simultaneously.…”
Section: Introductionmentioning
confidence: 99%